2002
DOI: 10.1007/s00299-002-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of the firefly luciferase gene in a barley ( Hordeum vulgare ) transformation system

Abstract: Transgenic lines of the spring barley variety Golden Promise containing the firefly luciferase gene were produced by particle bombardment of immature embryos. Non-destructive analysis of luciferase gene expression was used to monitor the transformation process. This revealed that transformation efficiency, in terms of the percentage of bombarded immature embryos giving rise to transformed callus lines, was very high, up to 40%. Following the expression of the luciferase gene provided a method for the sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Transformation efficiency has for many years been a limiting factor in studies requiring the production of large numbers of transgenic barley plants. Using biolistic-based methods to produce transgenic barley, it was demonstrated that the main block to achieving high transformation efficiencies was the ability to regenerate plants from transformed callus lines [ 14 ]. Following the first reports of Agrobacterium -mediated barley transformation [ 2 ], a comparison of the two methods revealed that the Agrobacterium -mediated method offered advantages in terms of lower copy number and more stable transgene expression [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation efficiency has for many years been a limiting factor in studies requiring the production of large numbers of transgenic barley plants. Using biolistic-based methods to produce transgenic barley, it was demonstrated that the main block to achieving high transformation efficiencies was the ability to regenerate plants from transformed callus lines [ 14 ]. Following the first reports of Agrobacterium -mediated barley transformation [ 2 ], a comparison of the two methods revealed that the Agrobacterium -mediated method offered advantages in terms of lower copy number and more stable transgene expression [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major constraint in the improvement of barley transformation efficiencies is the ability to successfully regenerate plants from transformed callus. It has previously been shown that plant transformation efficiencies have the potential to be as high as 40% if all transgenic callus lines, produced by particle bombardment, regenerated into independently transformed plants [ 14 ]. There have been a great number of studies examining factors affecting cereal transformation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…By using the modified medium, we were able to transform the two-rowed commercial malting barley cultivar Conlon (Manoharan and Dahleen 2002) and increase regeneration of the six-rowed barley Drummond (Dahleen and Bregitzer 2002). Experiments by Harwood et al (2002) also show that fertile green plant regeneration, rather than gene insertion, is a major roadblock to efficient barley transformation. Recent research showed that immature embryo explant size and ethylene concentration in vitro (Jha et al 2007) had major effects on regeneration.…”
Section: Future Directions: Opportunities and Challengesmentioning
confidence: 90%
“…Another nondestructive screenable marker used for barley transformation is the firefly luciferase gene. Harwood et al (2002) used particle bombardment to insert this gene under control of the maize ubiquitin promoter into Golden Promise embryos. The transformation efficiency, in terms of the percentage of bombarded immature embryos giving rise to transformed callus lines, was very high, up to 40%, but overall, only 1-2% of the bombarded calli regenerated plants.…”
Section: Markers In Transgenic Barleymentioning
confidence: 99%
“…The frequency of transformants was generally not very high between 1.7 and 7.0% of the immature embryos infected via Agrobacterium. On the other hand, it has been recently reported that the frequency is around 25% or higher [148][149][150]. Although the transformation frequency is lower, immature embryos still remain the target tissue of choice in barley [148,151].…”
Section: Barley Tissue Cultures and Gene Transfers Systemsmentioning
confidence: 99%